Oral nicorandil recaptures the waned protection from preconditioning in vivo - Iliodromitis, Efstathios K (2003)
1. Protection from preconditioning (PC) wanes and is eventually lost when multiple bouts of short ischemia or a prolonged reperfusion interval precedes the following sustained ischemia. The activation of mitochondrial K(ATP) channels plays a pivotal role in the intracellular signaling of PC. We tested whether the K(ATP) channel opener nicorandil (nic) preserves the given protection from PC in conditions where this benefit decays and is lost. 2. Eight groups of rabbits were divided into two equal series of experiments, one without nic (placebo) and one with nic treatment. Nic was given orally for 5 consecutive days in a dose of 5 mg kg(−1) d(−1). In a second step, four additional groups were treated with nic plus the K(ATP) channel blocker 5HD and 1 additional control group with nitroglycerin only. All the animals were anesthetized and then subjected to 30 min of myocardial ischemia and 2 h of reperfusion with one of the following interventions before the sustained ischemia: Control groups to no intervention; 3PC groups to three cycles of 5-min ischemia–10-min reperfusion; 8PC groups to eight cycles of 5-min ischemia – 10-min reperfusion; and 3PC90 groups to the same interventions as the 3PC groups but with a prolonged (90 min) intervening reperfusion interval before the sustained ischemia. The infarcted and the risk areas were expressed in percent. 3. There was no significant change in infarct size between the placebo, the nic and the 5HD-nic in the control groups (41.5±4.7, 43.9±7.1 and 48.7±6.4%) and 3PC groups (10.3±3.4, 12.2±3.9 and 12.6±4.5%). However, there was a significant decrease after nic treatment in groups 8PC (47.7±8.8% vs 13.0±2.6%, P<0.01) and 3PC90 (37.3±6.0% vs 14.2±2.4%, P<0.01), which was abrogated (38.2±4.7 and 42.7±4.4%, respectively, for 8PC and 3PC90 groups). Nitroglycerin had no effect on infarct size (39.1±3.1%, P=NS vs other controls). 4. Oral treatment with nic recaptures the waned protection of PC, both after repetitive bouts of short ischemia or after a prolonged reperfusion interval, preserving the initially obtained benefit. Nic by itself is insufficient to initiate PC in vivo.